Biomechanics and Fashion: Contributions for the Design of Clothing for the Elderly - Neves, Érica P. das [UNESP]; Brigatto, Aline C. [UNESP]; Medola, Fausto O. [UNESP]; Paschoarelli, Luis C. [UNESP] (Elsevier, 2015)
The aging population is a growing reality in many societies and is leading to significant changes in public health policies and the strengthening of the economic sector of these countries. This scenario intensified discussions about ageing and its determinants within several areas and thus substantially reflected on the design and the projective aspects of certain objects. It is due to cognitive and physical constraints of this group, which imply the need for differentiated products that are designed properly in favor of psychological, emotional, cognitive and physical well-being of the elderly. Once the clothing remains integrated with the body, its design and constructive aspects become essential in promoting positive experience in product usage. Understanding the factors present in the acquisition and use of clothing by the elderly are relevant to the design actions of these products. Therefore, considerations about their anatomical, biomechanical and psychological characteristics must be worked in order to ensure the integrity of the movements, as well as comfort, safety and inclusion of these individuals.
Keywords: elderly; ergonomic design; fashion